Designing the larssen type sheet pile shape with the increased bearing capacity - Nosenko, Oleg (Eastern-European Journal of Enterprise Technologies, 2016)
The paper deals with improving the Larssen sheet pile shapes on the basis of a new design concept of bending shapes. A new theoretical concept was developed, which consists in the fact that: – the design of shapes shall comply with the terms of rational material distribution in the cross-sectional plane of the shape; – an increase in the specific material consumption rate shall be ensured (W/G, cm3/kg); – the material concentration in the shape (W/F∙h) and the shape efficiency (W/F∙h∙Fw/Ffl) shall remain in the same range as those of the analogs. As a result, two sheet pile shapes with increased bearing capacity were designed. The first one, Larssen-7 shape (W=5010 cm3/m.sh.p.w.) was developed and adjusted for the conditions of production on the outdated rail and structural steel mill at the limit of its technical characteristics, and the second, Larssen 7H sheet pile shape (W=5200 cm3/m.sht.w) – on the new projected universal beam mill.